Andanças de um gato preto para além de um campo de neve : representações do Brasil e dos EUA na narrativa de viagem de Erico Veríssimo - Barbosa, Marcela Miller (2010)
Gato preto em campo de neve is the first travel book by Brazilian novelist Erico Verissimo. Responding to an invitation made by the American government in 1941, Verissimo departs on a three month journey from coast-to-coast across the United States. As result of his first experience abroad and due to its historical context, the account allows broaching issues related to national, regional and supranational identities that arise from the writer s encounter with the American culture, as well as the practices of cultural translation engendered by this encounter